Nigeria Annual International Conference and Exhibition 2010
DOI: 10.2118/136957-ms
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Local Bentonite with Imported Grade for Utilization in Oil Field Operations in Nigeria

Abstract: Bentonite is highly colloidal clay, which hydrates in water and greatly increases viscosity. Among others, it is added to fresh water mud to increase hole cleaning capability, reduce filtration into permeable formation, form a thin filter cake of low permeability and promote hole stability. However, up till date in Nigeria, most of the bentonite in use in oil field operations had been imported. Attempts to use the local bentonite had yielded little or no result because of its low yield and inability to meet up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…After, beneficiation with sodium bicarbonate, the local clay samples meet all the API standard required for viscosifier. Similar studies have been conducted by Joel and Nwokoye [5] and Apugo-Nwuso et al [6] and it was observed that all local samples used in their studies can attain the API specification for viscosifier when they are appropriately beneficiated. These studies have helped the oil policy makers in achieving their goal of local content as well as gearing towards development in their petroleum industry.…”
Section: Introductionsupporting
confidence: 78%
“…After, beneficiation with sodium bicarbonate, the local clay samples meet all the API standard required for viscosifier. Similar studies have been conducted by Joel and Nwokoye [5] and Apugo-Nwuso et al [6] and it was observed that all local samples used in their studies can attain the API specification for viscosifier when they are appropriately beneficiated. These studies have helped the oil policy makers in achieving their goal of local content as well as gearing towards development in their petroleum industry.…”
Section: Introductionsupporting
confidence: 78%
“…[1] Additionally, it is added to fresh water mud to enhance hole cleaning capability, form a thin filter cake of low permeability, lessen filtration into permeable formation, and promote well stability. [2][3][4] Bentonite particles may become aggregated under certain conditions including high temperatures, high concentrations, etc. [5] As a consequence, it is essential to add certain additives, that is, polymers, to make bentonie particles stable and prevent aggregation.…”
Section: Introductionmentioning
confidence: 99%